2003
DOI: 10.1238/physica.regular.068a00298
|View full text |Cite
|
Sign up to set email alerts
|

Local Spin Disorder in the Magnetic Kondo Compounds CeNi1-xCux

Abstract: We investigate the cosmological evolution of an interacting phantom energy model in which the phantom field interacts with the dark matter. We discuss the existence and stability of scaling solutions for two types of specific interactions. One is motivated by the conformal transformation in string theory and the other is motivated by analogy with dissipation. In the former case, there exist no scaling solutions. In the latter case, there exist stable scaling solutions, which may give a phenomenological solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 47 publications
(80 reference statements)
4
23
0
Order By: Relevance
“…In these examples, the different spin dynamics (namely multiple spin fluctuation rates) detected by the analysis of the μSR spectra are a signature of heterogeneous magnetic phases, including ordered clusters within the paramagnetic regime. 29 In the same way, our results on μSR spectroscopy give insight on the nature of the unusual paramagnetic state of ErCo 2 .…”
supporting
confidence: 57%
See 1 more Smart Citation
“…In these examples, the different spin dynamics (namely multiple spin fluctuation rates) detected by the analysis of the μSR spectra are a signature of heterogeneous magnetic phases, including ordered clusters within the paramagnetic regime. 29 In the same way, our results on μSR spectroscopy give insight on the nature of the unusual paramagnetic state of ErCo 2 .…”
supporting
confidence: 57%
“…The fact that muon is a microscopic probe of the magnetism on the sample which needs no large coherence length is relevant for the aim of the present study since it is very sensitive to short-range and other forms of disordered magnetism (cluster-glass, spin-glass). 29,30 A detailed description of muon spin relaxation spectroscopy can be found in Refs. 28, 31, 32, and 33.…”
mentioning
confidence: 99%
“…Thus, a SG-Kondo transition has been observed experimentally with increasing concentration in disordered alloys around the QCP. Recent experiments performed in CeNi 1 À x Cu x alloys have shown that the phase diagram of these alloys is more complicated [51,52]. In fact, when temperature decreases, for alloys with 0.7 > x > 0.1, there appears a ''cluster spin glass'' phase presenting magnetic inhomogeneities, rather than a classical SG phase.…”
Section: The Kondo Lattice-spin Glass Competitionmentioning
confidence: 99%
“…[53]. However, the experimental situation appears to be really complicate, as shown for example by recent experiments on CeN i 1−x Cu x alloys [51,52]. Thus, further experimental work is certainly necessary, but however the models presented here can account roughly for the behavior of heavy fermion disordered alloys, especially in the vicinity of the quantum critical point.…”
Section: The Kondo Lattice -Spin Glass Competitionmentioning
confidence: 91%
“…This is the case of the magnetic phase diagram of CeN i 1−x Cu x alloys that has been extensively studied [46,47] have shown that the phase diagram of these alloys is more complicate [51,52].…”
Section: The Kondo Lattice -Spin Glass Competitionmentioning
confidence: 99%